O novo (velho) homem: o masculino nos livros de autoajuda - Sônia Almeida; Bernardo Jablonski (Arquivos Brasileiros de Psicologia, 2011)
This work deals with the male image in the light of interpersonal communication, in two self-help books for couples: Why men don’t listen and women can’t read maps? by Pease and Pease, and Men are from Mars, Women are from Venus, by Gray. Taking into account social psychology approaches and some other related sciences, and in the methodology of UDUM - Underlying Discourse Unveiling Method, this work addresses the role of man under the view of self-help books. The discourse of these self-help books confirms the male image that can be seen in society and they provide tips that likely lead man to the same relationship issues. The results of this research highlight some possibilities of reaching a better understanding about the social cultural condition of the new man.